HIV incidence declines in a rural South African population: a G-imputation approach for inference - Vandormael, Alain; Cuadros, Diego; Dobra, Adrian; Bärnighausen, Till; Tanser, Frank (BMC public health, 2020)
Ad hoc assumptions about the unobserved infection event, which is known only to occur between the latest-negative and earliest-positive test dates, can lead to biased HIV incidence rate estimates. Using a G-imputation approach, we infer the infection dates from covariate data to estimate the HIV incidence rate in a hyper-endemic South African setting.